Cholecalciferol (vitamin D) differentially regulates antimicrobial peptide expression in bovine mammary epithelial cells: Implications during Staphylococcus aureus internalization - Téllez-Pérez, Ana Dolores; Alva-Murillo, Nayeli; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E. (Veterinary microbiology, 2012)
Vitamin D has immunomodulatory functions regulating the expression of host defense genes. The aim of this study was to determine the effect of cholecalciferol (vitamin D3) on S. aureus internalization into bovine mammary epithelial cells (bMEC) and antimicrobial peptide (AP) mRNA expression. Cholecalciferol (1–200nM) did not affect S. aureus growth and bMEC viability; but it reduced bacterial internalization into bMEC (15–74%). Also, bMEC showed a basal expression of all AP genes evaluated, which were induced by S. aureus. Cholecalciferol alone or together with bacteria diminished tracheal antimicrobial peptide (TAP) and bovine neutrophil β-defensin (BNBD) 5 mRNA expression; while alone induced the expression of lingual antimicrobial peptide (LAP), bovine β-defensin 1 (DEFB1) and bovine psoriasin (S100A7), which was inhibited in the presence of S. aureus. This compound (50nM) increased BNBD10 mRNA expression coinciding with the greatest reduction in S. aureus internalization. Genes of vitamin D pathway (25-hydroxylase and 1 α-hydroxylase) show basal expression, which was induced by cholecalciferol or bacteria. S. aureus induced vitamin D receptor (VDR) mRNA expression, but not in the presence of cholecalciferol. In conclusion, cholecalciferol can reduce S. aureus internalization and differentially regulates AP expression in bMEC. Thus, vitamin D could be an effective innate immunity modulator in mammary gland, which leads to a better defense against bacterial infection.